Evaluasi Pembelajaran Terpadu di PPMTI Tanjung Barulak Kampar: Studi Kualitatif tentang Cara Guru Menilai Santri di Pesantren Semi Modern. - Mely Cahyani; Miftahir Rizqa; Risnawati Risnawati (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study examines the integrated learning evaluation system implemented at the Modern Islamic Boarding School of Tarbiyah Islamiyah (PPMTI) Tanjung Barulak, Kampar Regency, Riau. As a semi-modern Islamic boarding school, PPMTI faces challenges in integrating traditional Islamic boarding school evaluation methods with modern evaluation approaches. This descriptive qualitative study aims to analyze how teachers assess students in integrated learning that combines the Islamic boarding school curriculum and the national curriculum. Data were collected through participatory observation, in-depth interviews with 12 teachers, and analysis of evaluation documents during the period March-May 2025. The results of the study indicate that PPMTI implements a holistic evaluation system that includes three main aspects: (1) cognitive evaluation through written and oral tests, (2) affective evaluation through observation of daily attitudes and morals, and (3) psychomotor evaluation through worship practices and skills. The findings indicate that the integration of traditional and modern evaluations results in a more comprehensive assessment of the development of students, but there are still challenges in standardizing and documenting evaluation results.